Mental Health and Its Associated Factors among Mental Health Professionals - Dhakshalini, N.; Rajkumar, A. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
Mental health is a fundamental component of overall well-being and significantly influences personal and professional performance. Mental health issues are common among mental health professionals due to the enormously stressful nature of their work. Objective of the study is to assess the mental health status and identifying associated factors among the mental health professionals working in Government Hospitals of Jaffna district. A cross-sectional study was carried out amongst 60 mental health professionals at government hospitals Jaffna. Five government hospitals were chosen for this study. Samples were collected through the purposive sampling method. Informed consent was obtained from all participants. The study incorporated both qualitative and quantitative data analysis. The study uses a self-made question, MHI-18 questionnaire. MHI -18 was validated and its Cronbach’s Alpha was 0.811 in the study. Anxiety, depression, behavioral control, positive affect are the four dimensions covered by MHI-18. Furthermore, interviews were carried out. Descriptive and Inferential analyses were used to analyze the data in SPSS (version 22) software. T-test, Correlation analysis, Chi-square test, Regression analyses were used for the study. Out of the 60 study participants, 24 (40%) were male and 36 (60%) were female mental health professionals. According to this study’s findings, 11.67% of mental health professionals reported having better mental health, 66.67% reported having good mental health, and 21.67% reported having poor mental health (X̅= 63.00, P value = 0.004). The findings emphasize that most of the mental health professionals exhibit good mental health status. Female mental health professionals have a higher level of anxiety than male mental health professionals (male X̅= 53.00, female X̅= 56.89, P value = 0.009). There is no difference in depression among mental health professionals in relation to marital status (Married X̅=71.78, single X̅= 72.80, P value = 0.368). Income does not significantly influence the mental health status of mental health professionals (Adjusted R2=0.031, P value = 0.095). Particularly, there is a strong correlation between anxiety and behavioral control of mental health professionals (P value =0.000) and there is a moderate correlation between the depression and religion of mental health professionals (P value =0.038). Mental health professionals have Good mental health, with a moderate presence of some mental health problems. Government, Hospital administration should look into these problems with greater urgency to come up with solutions that have good uptake and efficacy. Early screening, diagnosis, care and support should be made available to all the mental health professionals, as this will improve their mental health in the future.
Keywords: Anxiety; Depression; Mental health; Mental health professionals